Differing effect of modifiable cardiovascular risk factors on intima-media thickening and plaque formation at different sites of the arterial vasculature. Issue 19 (11th August 2010) - Chaubey, Sanjay; Nitsch, Dorothea; Altmann, Daniel; Ebrahim, Shah
Abstract : Objective: The effects of cardiovascular risk factors on the vascular anatomy at differing sites of the arterial vasculature have not been well described. The aim of this study was to compare the effect of cardiovascular risk factors on the intima media thickness (IMT) of the wall of the right and left common carotid artery (CCA) at their bifurcation and proximal from their bifurcation, and the effects on the presence of plaque at carotid and femoral arteries. Design: Cross-sectional population-based study. Setting/participants: Random samples of men (n=425) and women (n=367) aged 56–77 years were recruited from two general practices participating in the British Regional Heart Study. Main outcome measures: Ultrasound examination ascertained IMT and the presence of atheromatous plaque. A model for correlated outcomes was used to simultaneously model all risk factor on all measured vascular sites. Results: All cardiovascular risk factors (HbA1c, waist-to-hip ratio, hypertension, LDL and smoking) showed a larger association with IMT thickening at the wall of the CCA at its bifurcation than proximal to its bifurcation. The IMT was greater on the left wall of the CCA than on the right. The association between hypertension with the wall of the CCA depended on age. Smoking was the only risk factor that demonstrated an increased odds (45%, 95% CI 14% to 65%) of the presence of plaque at the femoral arteries when compared with the CCA. Conclusions: The associations of cardiovascular risk factors with the vascular anatomy are not uniform for IMT thickening or the presence of plaque. These differences in local arterial anatomy may result in differences between trial outcomes that investigate surrogate endpoints such as IMT.